2019
DOI: 10.1161/strokeaha.118.023580
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking History and Functional Outcomes After Spontaneous Intracerebral Hemorrhage

Abstract: Background and Purpose: While cigarette use may be a risk for intracerebral hemorrhage (ICH), animal models suggest that nicotine has a potential neuroprotective effect. The aim of this multicenter study is to determine the effect of smoking history on outcome in ICH patients. Methods: We analyzed prospectively collected data from the Ethnic/Racial Variations of Intracerebral Hemorrhage study, and included patients with smoking status data in the analysis. Patients were dichotomized into non-smokers versus eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…[ 37 , 42 – 44 ] The reason might be attributed to racial and socioeconomic differences, suggesting multi-nation and multi-center research to eliminate the potential bias. [ 45 48 ] Fourth, the data of therapeutic intervention was unavailable. As we know, medicine treatment plays a crucial role in ICH patients, notably patients without surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 , 42 – 44 ] The reason might be attributed to racial and socioeconomic differences, suggesting multi-nation and multi-center research to eliminate the potential bias. [ 45 48 ] Fourth, the data of therapeutic intervention was unavailable. As we know, medicine treatment plays a crucial role in ICH patients, notably patients without surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, cigarette smoking and nicotine had a detrimental effect in sICH patients in clinical studies ( Table 1 ) and in animal models from our laboratory (data not published). Some clinical studies also confirmed that no beneficial effect was seen after 3 months in sICH smoking patients [ 112 , 113 ]. The procoagulant benefit of cigarette smoking does not seem to be enough to overcome its detrimental effects.…”
Section: Potential Mechanisms By Which Tobacco Use Affects the Risk Omentioning
confidence: 93%
“…Some clinical studies also confirmed that no beneficial effect was seen after 3 months in sICH smoking patients. 112,113 The procoagulant benefit of cigarette smoking does not seem to be enough to overcome its detrimental effects.…”
Section: Potential Mechanisms By Which Tobacco Use Affects the Risk Of Sich And Outcome Following Sichmentioning
confidence: 99%
“…The worldwide annual incidence of spontaneous ICH is 12–35 per 100 000 population, which accounts for approximately 15% of cerebral strokes; it has a higher mortality rate compared with that of cerebral ischaemia. 13 The major high-risk factors for ICH are an elderly population, 14 male sex, 15 current smoking, 16 excessive alcohol consumption, 17 low total cholesterol level, 18 long sleep duration, 19 illicit drug use, 20 Asians ethnic origin 21 and genetic factors. 22 Other clinical disease can cause ICH, including hypertension, 23 coagulopathy, 24 cerebral amyloid angiopathy (CAA), 25 cerebral tumours, 26 intracranial arterial aneurysm, 27 vascular anomalies, 28 brain trauma, 29 premature birth, 30 haemorrhagic conversion of stroke, 31 posterior reversible encephalopathy syndrome, 32 vasculitis, 33 infective endocarditis, 34 dural arteriovenous fistula, 35 brain arteriovenous malformation, 36 cavernous malformation 37 and intracranial venous thrombosis 38 ( figure 1 ).…”
Section: Ich In the Clinical Settingmentioning
confidence: 99%